2009
DOI: 10.1249/mss.0b013e3181a6aaa4
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Assisted Cycling

Abstract: Intensity during cycling on an EAB, in all three measured conditions, is sufficiently high to contribute to the physical activity guidelines for moderate-intensity health-enhancing physical activity for adults (cutoff, 3 MET). Further study is needed to conclude whether these results still hold when using the EAB in regular daily life and in subjects with other fitness level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 13 publications
7
39
0
Order By: Relevance
“…This observation would be consistent with data from healthy adults, where 6 weeks of daily commuting was associated with an increase in maximal power output 18. In addition, we found that heart rate during e‐cycling was within the range sufficient to increase cardiorespiratory fitness and was comparable to experimental studies in younger healthy individuals where e‐cycling elicited a heart rate of 67–69% HR max over a flat circuit 15 and 80–84% HR max on an uphill route 14. Increased fitness through e‐cycling may be predictive of improvements in cardiometabolic risk factors 19, with a recent study reporting improved response to an oral glucose tolerance test in healthy individuals 20, suggesting that e‐cycling may have potential for improving glucose control in people with Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation would be consistent with data from healthy adults, where 6 weeks of daily commuting was associated with an increase in maximal power output 18. In addition, we found that heart rate during e‐cycling was within the range sufficient to increase cardiorespiratory fitness and was comparable to experimental studies in younger healthy individuals where e‐cycling elicited a heart rate of 67–69% HR max over a flat circuit 15 and 80–84% HR max on an uphill route 14. Increased fitness through e‐cycling may be predictive of improvements in cardiometabolic risk factors 19, with a recent study reporting improved response to an oral glucose tolerance test in healthy individuals 20, suggesting that e‐cycling may have potential for improving glucose control in people with Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…In healthy individuals, riding an e‐bike has been shown to provide physical activity of at least moderate intensity [>3 metabolic equivalents (METs); heart rate >65%] and generate improvements in fitness and cardiometabolic risk factors 13, 14, 15; however, to date, the acceptability/feasibility of ‘e‐cycling’ for people with Type 2 diabetes, or benefits to health are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Even when used on the highest power setting, the effort required is sufficient to count as at least moderate intensity physical activity (Gojanovic et al 2011;Simons, Van Es, and Hendriksen 2009). The intensity of electrically-assisted cycling is 'sufficiently high to contribute to the physical activity guidelines for moderate-intensity' (Simons, Van Es, andHendriksen 2009, 2097).…”
Section: E-velomobility Researchmentioning
confidence: 99%
“…Even when used on the highest power setting, the effort required is sufficient to count as at least moderate intensity physical activity (Gojanovic et al 2011;Simons, Van Es, and Hendriksen 2009). The intensity of electrically-assisted cycling is 'sufficiently high to contribute to the physical activity guidelines for moderate-intensity' (Simons, Van Es, andHendriksen 2009, 2097). If integrated into everyday life, for example by commuting to work by e-bike three times a week (riding to work with assistance, home without), and assuming the mean commuter cycling distance in the Netherlands of 4.3 km then the 'public health recommendations for physical activity are met' (2100).…”
Section: E-velomobility Researchmentioning
confidence: 99%
“…There is growing interest in the role that e-bikes can play in promoting health, and despite some concerns that electrically assisted cycling might not contribute sufficiently to minimum physical activity requirements (Simons et al, 2009; Sperlich et al, 2012), there is mounting empirical evidence to suggest that cycling with assistance can confer positive health benefits (Gojanovic et al, 2011; Louis et al, 2012). There are direct positive physical health outcomes.…”
Section: Introductionmentioning
confidence: 99%